Arteriosclerosis and the promise of GPIIb/IIIa inhibitors in stroke Arteriosclerosis y nuevas perspectivas de los inhibidores del receptor GPIIb/IIIa en stroke - GUSTAVO SAPOSNIK; LOUIS R CAPLAN (Arquivos de Neuro-Psiquiatria)
Ischemic mechanisms in patients with brain and heart attacks have been studied for more than 150 years. Antiplatelets agents did show benefit in secondary prevention. Aspirin is the most common antiaggregant in clinical use today. However, the benefit produced by the "best" antiplatelet regimen in stroke prevention is lower than 40%. The adherence of circulating platelets to the subendothelium is mediated by glycoprotein (GP) residing on the cell's surface. GPIIb/IIIa is the most important platelet membrane receptor that mediates the process of platelet aggregation, and thrombus formation. Thus, new drugs that block the GPIIb/IIIa receptor have recently emerged. Clinical trials using these agents have shown effectiveness in acute coronary syndromes. However, the absence of studies in cerebrovascular disease and the potential hemorrhagic complications questioned their use in stroke prevention. We review the clinical trials using the new GPIIb/IIIa agents in myocardial ischemia, and consider the potential implications for cerebrovascular disease. Los mecanismos de isquemia en infarto de miocardio y enfermedad cerebrovascular (ECV) han sido estudiados por mas de 150 años. Drogas antiplaquetarias mostraron un beneficio en la prevención secundaria. La aspirina es el mas común de los antiagregantes usados en la practica clínica. No obstante, el beneficio producido, aun con el "mejor" tratamiento antiagregante, en la prevención de ECV es inferior al 40%. La adhesión plaquetaria es un proceso mediado por glicoproteinas (GP) de la membrana celular. GPIIb/IIIa es un receptor de membrana plaquetaria que interviene en el proceso de agregación plaquetaria y formación del trombo. Estudios clínicos con nuevos agentes que bloquean a este receptor mostraron ser efectivos en los síndromes coronarios agudos. No obstante, la falta de estudios en ECV y las potenciales complicaciones hemorrágicas, limitan su uso en la prevención de stroke. Revisamos los mecanismos de trombogenésis y los estudios clínicos con los nuevos agentes GPIIb/IIIa, considerando sus implicancias en ECV.